Resisting Reagan the U.S. Central America peace movement - Smith, Christian, 1960- (University of Chicago Press, 1996)
"Though more a study of US interest groups and social movements, provides useful information on US policy toward Central America. Somewhat sympathetic toward the peace movements' goals and to their definition of 'harassment.'"--Handbook of Latin American Studies, v. 57.